The Relationship between Sleep Hygiene and Sleep Disorders in Elementary School Age Children in Grades 5-6 at Sdn 11 Telaga Biru, Gorontalo Regency - Nurhalizah Hi Kader; Dewi Modjo; Lenny Ali; Indrawati (Universitas Muhammadiyah Palu, 2026)
Sleep is a fundamental physiological process for the recovery of body organs and the optimization of children's cognitive function. However, many children experience sleep disorders, which are conditions that disrupt normal sleep patterns, both in terms of duration, quality, and sleep time. One of the triggers is poor sleep hygiene, which is a series of behavioral habits and environmental settings designed to support healthy sleep. This study aims to analyze the relationship between sleep hygiene and sleep disorders in students in grades 5-6 at SDN 11 Telaga Biru. The study used a quantitative method with a cross-sectional design involving 44 students as a sample (total sampling). Data were collected using the Sleep Hygiene Index (SHI) and Sleep Disturbance Scale For Children (SDSC) questionnaires, then analyzed bivariately using the Fisher's Exact Test. The findings showed that the majority of respondents had moderate hygiene (50%) and experienced severe sleep disorders (59.1%). The results of the statistical test obtained a p-value of 0.000 (p < 0.05), which proves that there is a significant relationship between sleep hygiene and sleep disorders. The worse the implementation of healthy sleep habits, the higher the risk of children experiencing severe sleep disorders. There is a real link between daily sleep behavior and the appearance of sleep disorders in children.